2018
DOI: 10.3390/ijms19113328
|View full text |Cite
|
Sign up to set email alerts
|

IL-18 and S100A12 Are Upregulated in Experimental Central Retinal Vein Occlusion

Abstract: Retinal vein occlusion (RVO) is a common retinal vascular disease. RVO may be complicated by pronounced ischemia that often leads to severe loss of visual function. The present work aimed at studying the retinal proteome of RVO complicated by ischemia. In six Danish Landrace pigs RVO was induced with argon laser in the right eye of each animal. As four retinal veins were occluded, the RVO best corresponded to a central retinal vein occlusion (CRVO). Left control eyes received a similar laser treatment without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
36
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 53 publications
7
36
0
1
Order By: Relevance
“…S100A7, S100A8, and S100A9 belong to the S100 protein family of small calcium-binding proteins 42 that contribute to lipopolysaccharide response in a TLR4 dependent manner. 42 We have previously suggested that proteins of the S100 family are regulated in retinal vein occlusion 22 and our study indicates that the turnover of S100 proteins is altered in BRVO. However, the S100 proteins did not correlate with CRT and BCVA, and our data does not provide an underlying explanation for the S100 regulation.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…S100A7, S100A8, and S100A9 belong to the S100 protein family of small calcium-binding proteins 42 that contribute to lipopolysaccharide response in a TLR4 dependent manner. 42 We have previously suggested that proteins of the S100 family are regulated in retinal vein occlusion 22 and our study indicates that the turnover of S100 proteins is altered in BRVO. However, the S100 proteins did not correlate with CRT and BCVA, and our data does not provide an underlying explanation for the S100 regulation.…”
Section: Discussionsupporting
confidence: 58%
“…Mass spectrometry data were further processed with Perseus software version 1.6.2.3 (Max Planck Institute of Biochemistry, Martinsried, Germany; https://maxquant.net/perseus/ ) to remove poorly identified proteins as described in a previous article. 22 LFQ values were log 2 transformed, and mean LFQ values were calculated. At least two unique peptides were required for successful protein identification.…”
Section: Methodsmentioning
confidence: 99%
“…Coincidentally, individuals with RVO are also at a significantly greater risk of developing ischemic and hemorrhagic strokes (Chen et al, 2018). In one study, RVO was induced in pigs, which led to a reduction in proteins involved in vision, such as rhodopsin (Cehofski et al, 2018). This compromise in rhodopsin function suggests that neurotransmission is sensitive to ischemic insult.…”
Section: Rhodopsin and Strokementioning
confidence: 99%
“…Animals were housed under a 12 h light/dark cycle. Anesthesia, topical anesthesia with eye drops, and dilation of the pupils were performed as previously described [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Mass spectrometry data was processed further with Perseus software version 1.6.2.3 [ 28 ] to remove poorly identified proteins as described in a previous article [ 22 ]. LFQ values were log2-transformed.…”
Section: Methodsmentioning
confidence: 99%